Relações entre tédio e trabalho na contemporaneidade - Oliveira, Adriana Aparecida Almeida de; Justo, José Sterza [UNESP] (My University, 2011)
This study is a theoretical investigation which intends to discuss possible relationships between work and boredom based on notable authors and theories. Unlike modern industrial societies centered mainly in production, new societies are characterized by increased consumption. The meaningless work and non-productive and prospective consumption leads the subject to be only a digestive organ providing favorable conditions for the presence of boredom, a mode of subjectivation characterized by a status of unconcern for the world, i.e. a low-intensity lifestyle.

O presente trabalho é uma reflexão teórica que procura discutir, a partir de autores e teorias consagradas, as possíveis relações entre o trabalho e o tédio na contemporaneidade. Diferentemente das sociedades industriais modernas, centradas principalmente na produção, as atuais são caracterizadas pela ênfase no consumo. O trabalho despojado de sentido para a existência e o consumo abdicador de ações criadoras e produtoras, tornam o sujeito apenas um organismo digestivo criando condições propícias para o aparecimento do tédio, um modo de subjetivação marcado por um estado de desinteresse pelo mundo, enfim, uma vida de baixa intensidade.
Relationships between boredom and work in the contemporaneousness
Keywords: Contemporaneousness; Work and boredom; Contemporaneidade; Trabalho e tédio